2017
DOI: 10.1590/1980-5373-mr-2016-0964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LZSA Glass-Ceramic Addition on Pressureless Sintered Alumina. Part I: Grain Growth

Abstract: The aim of this study was to evaluate the effect of an 11.6Li 2 O-16.8ZrO 2 -68.2SiO 2 -3.4Al 2 O 3 (LZSA) glass ceramic on the grain growth of alumina obtained by pressureless sintering. Three contents of the LZSA glass ceramic (7, 15, and 21 vol%; mean particle size of 1.52 µm) and three types of alumina (mean particle sizes of 0.5, 1.7, and 2.8 µm) were used. The powder compositions were formed by cold pressing. The samples (5 mm × 5 mm × 13 mm) were sintered in an optical dilatometer. The grain size and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Part I of this work demonstrated the effect of an LZSA glass-ceramic on the grain growth of alumina 25 , since the grain size is one of the most important microstructural features that must be controlled in order to obtain high performance alumina. Microstructural control by means of dopants and processing techniques can improve the mechanical properties of alumina-wear for example 16 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Part I of this work demonstrated the effect of an LZSA glass-ceramic on the grain growth of alumina 25 , since the grain size is one of the most important microstructural features that must be controlled in order to obtain high performance alumina. Microstructural control by means of dopants and processing techniques can improve the mechanical properties of alumina-wear for example 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Five compositions were prepared from an LZSA glassceramic composition (Tecnofrita, Brazil) and three grades of alumina (99.8 wt% of Al 2 O 3 , Almatis, USA); the chemical composition, particle size, and specific surface area of these materials were presented in the previous work 25 . The experimental design used two factors: the particle size of alumina and the glass-ceramic content varied on two levels (−1 and +1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, previous works (Montedo et al, 2017;Montedo et al, 2018) investigated the addition of 21 vol% of a 11.6Li 2 O-16.8ZrO 2 -68.2SiO 2 -3.4Al 2 O 3 (mol%) glass-ceramic to a fine grain alumina, sintered at 1470 ºC and 3 h holding time (2% porosity). They observed that the glass-ceramic addition caused a much more significant effect on the mechanical properties than the initial particle size of alumina.…”
Section: Introductionmentioning
confidence: 99%